B lymphocyte subsets and outcomes in patients with an initial diagnosis of transient hypogammaglobulinemia of infancy. (26th September 2018) - Eroglu, Fehime K.; Aerts Kaya, Fatima; Cagdas, Deniz; Özgür, Tuba Turul; Yılmaz, Togay; Tezcan, İlhan; Sanal, Özden
Abstract: Purpose: Transient hypogammaglobulinemia of infancy (THI) is a common immunodeficiency, but definitive diagnosis can only be made retrospectively. While the pathogenesis is still unknown, abnormalities have been reported in the B cell compartment. In this study, we analysed the B cell subsets of patients with an initial THI diagnosis (n = 20) and compared them with those of healthy age‐matched Turkish children (n = 72). Methods: Flow cytometric analyses of the B subsets were performed by staining with anti‐CD27‐PE, anti‐CD19‐PerCP, anti‐IgD‐FITC and anti‐IgM‐APC antibodies. Results: During a median follow‐up of 6.6 years, 13 patients whose IgG levels had normalized before they reached four years of age were diagnosed with definitive THI. The memory subsets of these patients were lower but not statistically different from the healthy controls (HC). The remaining seven patients had prolonged hypogammaglobulinemia after the age of four and had significantly lower memory B cell subsets compared to the HC. On follow‐up, these patients had not experienced recurrent infections or autoimmunity. Re‐evaluation of patients' B cell subsets six years later showed that the memory B cell ratios had increased to levels comparable to HC, despite the patients still having mildly low IgG levels. Conclusion: Patients with prolonged hypogammaglobulinemia had lower levels of memory B cells despite having a similar clinical course to patients who had been diagnosed with definitive THI. This subgroup of putative THI patients poses a diagnostic and classification dilemma. Our results suggested that these patients' memory B cells and IgG levels may recover over time.